Maudhui Qualitative Framework: A New Concept for Spiritual Value-Based Social Research - Abid Nurhuda (PT. Caesarindo Triloka Persada, 2025)
This article proposes the Maudhui Qualitative Framework as a new concept that integrates the thematic interpretation (maudhui) approach with qualitative methodology in interpreting social reality. This framework is built on the assumption that knowledge is not solely the result of empirical observation, but also the result of a dialogue between normative texts, social experiences, and spiritual horizons. With an analytical structure consisting of theme identification, qualitative data collection, hermeneutic-thematic analysis, and the formulation of transformative values, this framework presents a coherent, flexible, and transdisciplinary methodological alternative. The article's main findings confirm that the Maudhui Qualitative Framework can enrich social research with ethical and transcendental dimensions that have been neglected by the dominant paradigm. Its implications are not only significant for the development of values-based social science but also provide practical direction for more just, inclusive, and humane social change. Thus, the Maudhui Qualitative Framework can be positioned as a new paradigm that positions social research not only as an academic process, but also as a path to civilizational transformation.